2019
DOI: 10.1016/j.mayocpiqo.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Heart Disease and Dietary Carbohydrate, Glycemic Index, and Glycemic Load: Dose-Response Meta-analyses of Prospective Cohort Studies

Abstract: ObjectiveTo clarify the role of dietary carbohydrate, glycemic index (GI), and glycemic load (GL) in progression from health to coronary heart disease (CHD) by determining disease-nutrient risk relation (RR) values needed for intake ranges within jurisdictions and across the globe.MethodsWe performed a literature search of MEDLINE and EMBASE for prospective cohort studies that used truly valid dietary instruments in heathy adults published from January 1, 2000, to June 5, 2018. Relevant observations were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
2
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 80 publications
(197 reference statements)
1
84
2
10
Order By: Relevance
“…Further, only one meta-analysis [9] restricted their study selection to those applying truly valid dietary instruments, which were for nutrient amounts in general (validity correlation > 0.5) [18]. For GI and GL, a validity correlation for carbohydrate > 0.55 is considered appropriate when assessing coronary heart disease and GI and GL risk relations [19], and was applied here. This higher value (0.55) was selected based on the study of Brunner et al [18], who recommended, in general, a value of 0.5 for nutrients, which was adopted by Barclay et al in 2008 [9] in their studies of T2D GI and GL risk ratios, to which 10% was added to allow for any error of the estimation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, only one meta-analysis [9] restricted their study selection to those applying truly valid dietary instruments, which were for nutrient amounts in general (validity correlation > 0.5) [18]. For GI and GL, a validity correlation for carbohydrate > 0.55 is considered appropriate when assessing coronary heart disease and GI and GL risk relations [19], and was applied here. This higher value (0.55) was selected based on the study of Brunner et al [18], who recommended, in general, a value of 0.5 for nutrients, which was adopted by Barclay et al in 2008 [9] in their studies of T2D GI and GL risk ratios, to which 10% was added to allow for any error of the estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we updated the meta-analyses (as in [9]) for both GI and GL, again using studies with truly valid dietary instruments. A difference is that we defined a truly valid dietary instrument as one that has a validity correlation > 0.55 for carbohydrates [19] rather than 0.5 for nutrients in general. A further difference is that we used preferred quantitative dose–response meta-analysis (DRM) [5,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systemic review and meta-analysis of prospective cohorts, Reynolds et al [ 16 ] concluded that, compared with dietary fibre and whole grains, the GI might not be as useful a measure of carbohydrate quality for the prevention of chronic disease. Conversely, subsequent dose–response meta-analyses of prospective cohorts showed that the risk of coronary heart disease and type 2 diabetes increased by 24% and 27% per 10 unit increase in GI, respectively [ 97 , 98 ]. Food Standards Australia New Zealand permits “low,” “medium,” and “high” GI claims.…”
Section: Labelling Foods For Carbohydrate Qualitymentioning
confidence: 99%
“…The most frequently accessed article on our website (www. mcpiqojournal.org) was a case report on unusual presentations of vitamin B 12 deficiency 12 (6,060 requests), followed by an article on the relationship between dog ownership and cardiovascular health 13 (3,195) and a dose-response meta-analysis of coronary heart disease and dietary carbohydrates 14 (590). The most frequently accessed articles on ScienceDirect.com addressed worksite wellness intervention 15 (729 requests), cost comparison of different approaches to sedation during gastrointestinal endoscopy, 16 (455) and a case report on immunemediated cerebellitis with immune checkpoint inhibitor therapy (410).…”
mentioning
confidence: 99%